2019
DOI: 10.1158/1541-7786.mcr-19-0436
|View full text |Cite
|
Sign up to set email alerts
|

GPR56 Drives Colorectal Tumor Growth and Promotes Drug Resistance through Upregulation of MDR1 Expression via a RhoA-Mediated Mechanism

Abstract: Drug resistance continues to be a major obstacle of effective therapy for colorectal cancer, leading to tumor relapse or treatment failure. Cancer stem cells (CSC) or tumor-initiating cells are a subpopulation of tumor cells which retain the capacity for self-renewal and are suggested to be implicated in drug resistance. LGR5 is highly expressed in colorectal cancer and marks CSCs that drive tumor growth and metastasis. LGR5( þ ) CSCs cells were shown to interconvert with more drug-resistant LGR5( À ) cancer c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 48 publications
1
80
0
Order By: Relevance
“…For example, miR-27a was decreased in bladder cancer and restored miR-27a re-sensitized cisplatin resistance by targeting the cystine/glutamate exchanger SLC7A11 (27). miR-340-5p was reduced in breast cancer, and its overexpression inhibited drug resistance to docetaxel by targeting LRG5 via the Wnt/β-catenin pathway (28,29). We previously found that low expression of miR-15b and miR-16 was detected in drug-resistant GC cells, which medicated sensitivity to vincristine (VCR) by directly regulating Bcl-2 (30).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-27a was decreased in bladder cancer and restored miR-27a re-sensitized cisplatin resistance by targeting the cystine/glutamate exchanger SLC7A11 (27). miR-340-5p was reduced in breast cancer, and its overexpression inhibited drug resistance to docetaxel by targeting LRG5 via the Wnt/β-catenin pathway (28,29). We previously found that low expression of miR-15b and miR-16 was detected in drug-resistant GC cells, which medicated sensitivity to vincristine (VCR) by directly regulating Bcl-2 (30).…”
Section: Introductionmentioning
confidence: 99%
“…GPR56 has been shown to induce activation of the small GTPase RhoA mediated through Gα12/13 to promote cell adhesion (13,20,(24)(25)(26). To examine if mutant GPR56 STP was fully functional, we utilized a GTPase pulldown assay that employs the Rho binding domain of the Rho effector, Rhotekin.…”
Section: Gpr56 Overexpression Activates Srf-re Independent Of the Stpmentioning
confidence: 99%
“…GPR56 is upregulated in cancers of the breast, lung, ovary, pancreas, colon and glioblastoma (9)(10)(11). Analysis of clinical data revealed a significant correlation between high GPR56 levels and poor outcome in acute myeloid leukemia, ovarian cancer, and colorectal cancer (CRC) (10)(11)(12)(13)(14)(15). In CRC, GPR56 was shown to promote drug resistance and drive tumor growth (12,13,16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations